Light‐Emitting Diode treatment ameliorates allergic lung inflammation in experimental model of asthma induced by ovalbumin. Issue 12 (18th April 2017) - Siqueira, Vanessa Perosino Cardoso; Evangelista, Marina Izadora Silveira; dos Santos, Alana; Marcos, Rodrigo Labat; Ligeiro‐de‐Oliveira, Ana Paula; Pavani, Christiane; Damazo, Amílcar Sabino; Lino‐dos‐Santos‐Franco, Adriana
Abstract: Since asthma is a multifactorial disease where treatment sometimes is not effective, new therapies that improve the respiratory discomfort of patients are of great importance. Phototherapy as Light‐emitting diode (LED) has emerged as a treatment that presents good results for diseases that are characterized by inflammation. Thus, our objective was to investigate the effects of LED on lung inflammation, by an evaluation of lung cell infiltration, mucus secretion, oedema, and the production of cytokines. Male Balb/c mice were or not sensitized and challenged with ovalbumin (OVA) and treated or not with LED therapy (1 h and 4 h after each OVA challenge). Twenty‐four hours after the last OVA challenge, analyzes were performed. Our results showed that LED treatment in asthmatic mice reduced the lung cell infiltration, the mucus production, the oedema, and the tracheal's contractile response. It also increased the IL‐10 and the IFN‐gamma levels. The effects of LED treatment on lung inflammation may be modulated by IL‐10, IFN‐gamma, and by mast cells. This study may provide important information about the effects of LED, and in addition, it may open the possibility of a new approach for the treatment of asthma. Abstract : Asthma is a multifactorial disease where treatment sometimes is not effective and, in this context new therapies are of great importance. Phototherapy as Light‐emitting diode (LED) has emerged as a promisor treatment presenting good results for diseases which are characterized by inflammation. This study open the possibility of a new approach for the asthma treatment showing that drug therapy chould be replaced by LED treatment.